(untitled) (Journal of Civil Engineering Researchers, 2023)
Nowadays, the use of reinforced concrete hollow slab system in building structures is widely accepted due to the provision of control criteria, the ability to be used in large openings and flexibility in architectural designs, and it is more responsive in terms of economic efficiency and time management. has it. The use of reinforced concrete hollow slabs is one of the effective methods in styling and reducing the dead load and consequently the earthquake load, and as a result achieving sections with smaller dimensions. The aim of the current research is to study the post-cracking behavior of reinforced concrete hollow slabs under Common loading situations and analyzed using the finite element method. Also, by using the obtained results and comparing them with the behavior of laboratory samples, it is intended to determine the optimal numerical model for predicting the behavior of reinforced concrete hollow slab, and to measure the accuracy of common design relationships. Modeling of hollow concrete slab sample in this study has been done using ABAQUS software, and the results of this study showed; The load coincident with the first crack in the CDP method was obtained for 10.18, 15.2, 34.20, and 44 for the concentrated joint, concentrated grip, wide joint, and wide grip modes, respectively.